TECHNIQUE OF PRODUCING SPHERICAL SHELL BEADS AS NUCLEI FOR CULTURED PEARLS - Velu, M; Alagarswamy, K; Qasim, S Z (Indian Journal of Fisheries, 2011)
A process for the production of spherical beads from the shells of the Indian conch,Xancuspyrum, has been developed. These beads are used as nuclei for cultured pearls.The equipment consists of a grinding attachment fitted to an ordinary bench drill. Twopairs of carborundum wheels, coarse and fine, are used for grinding the beads. Thefinished beads compare favourably with those used in the pearl culture trade in Japan